2011
DOI: 10.1080/13607863.2010.551340
|View full text |Cite
|
Sign up to set email alerts
|

Is reciprocity always beneficial? Age differences in the association between support balance and life satisfaction

Abstract: Age, type of support, and source of support should be considered when studying the relationships between support balance and psychological well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 28 publications
4
41
0
2
Order By: Relevance
“…Unbalanced social exchanges increase depressive symptoms and psychological distress (Li, Fok, & Fung, 2011). This is likely because inequity reveals the unequal need for social support and thus hardship, and unequal exchanges also rebuke norms of reciprocity (Henretta, Hill, Li, Soldo, & Wolf, 1997; Silverstein, Conroy, Wang, Giarrusso, & Bengtson, 2002).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Unbalanced social exchanges increase depressive symptoms and psychological distress (Li, Fok, & Fung, 2011). This is likely because inequity reveals the unequal need for social support and thus hardship, and unequal exchanges also rebuke norms of reciprocity (Henretta, Hill, Li, Soldo, & Wolf, 1997; Silverstein, Conroy, Wang, Giarrusso, & Bengtson, 2002).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…In their study, only providing support to others was positively related to quality of life; receiving support was negatively related to quality of life. In contrast, Li et al [20] reported that overbenefited friendships are more strongly associated with life satisfaction than reciprocal friendships, which indicates a crucial role for received rather than provided support. However, as all these studies are cross-sectional, an alternative explanation that greater well-being promotes a coherent perception of social exchange cannot be excluded.…”
Section: Introductionmentioning
confidence: 97%
“…What makes peer support so complex is that one central aspect of peer support relationships is that they are likely to be reciprocal (Kram 1985), such that the actors both give and receive support in a relationship. Reciprocity therefore considers pairs of directed ties that are either binary (present and absent) or weighted (e.g., by frequency or strength; Squartini et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A second central aspect is that peer support relationships are rarely one-dimensional. Rather, they are likely to be multiplex (Kram 1985), such that a single relationship comprises various types of support exchanged between the actors (Dobrow et al 2012;Rodkin and Ryan 2012). This multiplexity can be mapped by incorporating layers into the social support network, one for each different support type (Gemmetto et al 2016).…”
Section: Introductionmentioning
confidence: 99%